Thermoelectric properties of LaCo4Sb12 skutterudite materials by addition of Al, In, Ni & Te / Mohamed Bashir Ali Bashir - Mohamed Bashir, Ali Bashir (2017)
Skutterudite is a superior material used in thermoelectric application. In this work, the crystal structure and morphology of the ternary skutterudite (La/Yb)xCo4Sb12 were modified by incorporating of various addition such as Al, In, Ni and Te. This process was conducted via two step method namely mechanical alloying and spark plasma sintering technique. Specifically, the phase structure and morphology of the bulk samples were examined by X-ray diffraction (XRD) and scanning electron microscopy integrated energy-dispersive X-ray spectroscopy analysis (SEM-EDS), respectively. The thermoelectric properties of the bulk samples were measured in a temperature range of 300 K to 800 K. Furthermore, the oxidation and thermal properties of the samples were studied using a thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) that measured from 25 °C to 1000 °C. Evidently, it is proved that all of the samples demonstrated a dominant phase of polycrystalline CoSb3 skutterudite. Among the sample, Al0.05La0.5Co4Sb12 exhibited an excellent electrical properties, as manifested by its optimum carrier concentration and lowest electrical resistivity of 7.6μΩm at 314 K. In terms of the Seebeck coefficient, La0.5Co4Sb11.7Te0.3 recorded a highest value of 300 μV/K at 404 K. In the thermal conductivity behaviors, Al0.3La0.5Co4Sb12 sample showed the lowest thermal conductivity and lattice thermal conductivity values of 1.1 W/mK (314 K) and 0.64 W/mK (595 K), respectively. This occurrence can be related to the enhancement in phonon scattering by rattling Al atom into the lattice cages. Al0.05La0.5Co4Sb12 also presented a highest dimensionless figure of merit (ZT) which is 1.36 at 789 K, validating the substantial mitigation in electrical resistivity and lattice thermal conductivity. In conclusion, it has been proven that the modified materials possess notable oxidation and thermal stability in high temperature regime up to 800 °C.